2013
DOI: 10.1186/1471-2458-13-654
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in self-rated health among 45+ year-olds in Almaty, Kazakhstan: a cross-sectional study

Abstract: BackgroundSelf-rated health (SRH) has been widely studied to assess health inequalities in both developed and developing countries. However, no studies have been performed in Central Asia. The aim of the study was to assess gender-, ethnic-, and social inequalities in SRH in Almaty, Kazakhstan.MethodsAltogether, 1500 randomly selected adults aged 45 years or older were invited to participate in a cross-sectional study and 1199 agreed (response rate 80%). SRH was classified as poor, satisfactory, good and excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
2
13
1
Order By: Relevance
“…There is evidence that the social gradient in obesity changes with affluence and development; at earlier stages of transition, obesity shows a positive association with socioeconomic status but at later stages the gradient becomes inverse. [31] The higher prevalence of diabetes in ethnic Russians is analogous to previously reported lower self-rated health in the Russian vs. Kazakh ethnicity [32,33], however, in contrast to self-rated health, the difference for diabetes prevalence was only marginally statistically significant. While the increased risk in Russians may be related to life style of socioeconomic status, it was not attenuated in the fully adjusted model.…”
Section: Discussionsupporting
confidence: 75%
“…There is evidence that the social gradient in obesity changes with affluence and development; at earlier stages of transition, obesity shows a positive association with socioeconomic status but at later stages the gradient becomes inverse. [31] The higher prevalence of diabetes in ethnic Russians is analogous to previously reported lower self-rated health in the Russian vs. Kazakh ethnicity [32,33], however, in contrast to self-rated health, the difference for diabetes prevalence was only marginally statistically significant. While the increased risk in Russians may be related to life style of socioeconomic status, it was not attenuated in the fully adjusted model.…”
Section: Discussionsupporting
confidence: 75%
“…Socioeconomic conditions and the decrease in family income are linked to poor health indicators [ 25 , 26 ]. Aittomäki et al (2012, 2014) used longitudinal data to analyze how health inequalities are associated with the specifics of the labor market and family income [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that SRH is a strong predictor of health outcomes and mortality, independent of many biological and physical factors (Jylha 2009 ; Mavaddat et al 2011 ; Kaplan and Baron-Epel 2003 ; Supiyev et al 2014 ). In population studies, SRH has been shown to be a feasible, inclusive, and informative measure of health (Jylha 2009 ; Abikulova et al 2013 ; Idler and Benyamini 1997 ). A review of 27 community studies showed SRH was a predictor of mortality in nearly all of the studies, even after controlling for other relevant health indicators and covariates known to predict mortality (Idler and Benyamini 1997 ; Surkan et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%